The Impact of the Cash Transfer Program on Poverty of Households in Bogor Regency: BIG, IPB University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
The Covid-19 pandemic caused that the number of poor people increase more than 26 million people on March 2020.  That is the highest since 2017. To save the lives of poor families affected by the pandemic, the Government through the Ministry of Social Affairs is maximizing the Bantuan Sosial Tunai (BST) program. This research aims to examine the impact of the BST program on poverty of households that received BST program in Bogor Regency. This study used a quasi experimental by dividing households into the treatment group and the control group. The treatment group in this study were households that received the BST program. While the control group is households that do not receive the BST program. This study used primary data from 80 households in Karihkil Village, Ciseeng District, Bogor Regency. To get a control group that is similar to the treatment group, the study used the propensity score matching (PSM) method with the Probit model. The quantitative analysis method used in this research is the difference in difference (DID) method. The research show that the BST program does not have a significant impact on poverty of households in Bogor Regency.